Gymnopilus dilepis, a new record in Thailand - Nakarin Suwannarach (2018)
Specimens collected in Thailand have been identified as Gymnopilus dilepis, based on morphology and ITS molecular analysis. A description and illustration are provided. This is the first record of this fungus from Thailand.